"Engi er allheimskr, ef þegja má": Women and Silence in the Sagas and þættir of Icelanders - Wolf, Kirsten (Maal og Minne, 2018)
It is well known that women in medieval Iceland had limited opportunity to take part in political and legal affairs, but that often they were able to somewhat influence the political and legal structures affecting their lives by being quite verbal. While acknowleding the importance of women’s words and, by extension, the fact that power is routinely exercized through speech, this article draws attention to the fact that, paradoxically, silence was also an important tool available to women in medieval Iceland. An examination of the Sagas and þættir of Icelanders reveals that women used and relied on non-verbal expression in their interactions with men in order to achieve their goals. University of Wisconsinâ€”Madison